A 12-month prospective cohort study of symptoms of common mental disorders among professional rugby players. Issue 7 (9th August 2018) - Gouttebarge, Vincent; Hopley, Philip; Kerkhoffs, Gino; Verhagen, Evert; Viljoen, Wayne; Wylleman, Paul; Lambert, Mike
Abstract: The primary aims were to determine the 12-month incidence (and comorbidity) of symptoms of common mental disorders (CMD) among male professional rugby players and to explore their association with potential stressors. A secondary aim was to explore the view of male professional rugby players about the consequences of symptoms of CMD and related medical support/needs. An observational prospective cohort study with three measurements over a 12-month period was conducted among male professional rugby players from several countries. Symptoms of CMD (distress, anxiety/depression, sleep disturbance, eating disorders and adverse alcohol use) and stressors (adverse life events, rugby career dissatisfaction) were assessed through validated questionnaires. A total of 595 players (mean age of 26 years; mean career duration of 6 years) were enrolled, of which 333 completed the follow-up period. The incidence of symptoms of CMD were: 11% for distress, 28% for anxiety/depression, 12% for sleep disturbance, 11% for eating disorders and 22% for adverse alcohol use (13% for two simultaneous symptoms of CMD). Professional rugby players reporting recent adverse life events or career dissatisfaction were more likely to report symptoms of CMD but statistically significant associations were not found. Around 95% of the participants stated that symptoms of CMD can negatively influence rugby performances, while 46% mentioned that specific support measures for players were not available in professional rugby. Supportive and preventive measures directed towards symptoms of CMD should be developed to improve not only awareness and psychological resilience of rugby players but also their rugby performance and quality-of-life.